Progress report on Health and Sanitation Project (HSP): period April'94 - June'95, a view of Dulhazra Gram Kendra - Khandakar, A. Q. (© BRAC, 2016)
1. Introduction 2. Aims and objectives of the project 3. Project area 4. Relief culture 5. Socioeconomic survey 6. Data collection and presentation 7. Recruitment of Village Organizer (VO) 8. Achievement of HSP at a glance 9. Formation of Village Based Institutions (VBIs) 10. Monitoring and supervision